Efficient CRISPR-Cas13d-Based Antiviral Strategy to Combat SARS-CoV-2 - Hussein, Mouraya; Andrade dos Ramos, Zaria; Vink, Monique A.; Kroon, Pascal; Yu, Zhenghao; Enjuanes, Luis; Zuñiga, Sonia; Berkhout, Ben; Herrera-Carrillo, Elena (Viruses, 2023)
The current SARS-CoV-2 pandemic forms a major global health burden. Although protective vaccines are available, concerns remain as new virus variants continue to appear. CRISPR-based gene-editing approaches offer an attractive therapeutic strategy as the CRISPR-RNA (crRNA) can be adjusted rapidly to accommodate a new viral genome sequence. This study aimed at using the RNA-targeting CRISPR-Cas13d system to attack highly conserved sequences in the viral RNA genome, thereby preparing for future zoonotic outbreaks of other coronaviruses. We designed 29 crRNAs targeting highly conserved sequences along the complete SARS-CoV-2 genome. Several crRNAs demonstrated efficient silencing of a reporter with the matching viral target sequence and efficient inhibition of a SARS-CoV-2 replicon. The crRNAs that suppress SARS-CoV-2 were also able to suppress SARS-CoV, thus demonstrating the breadth of this antiviral strategy. Strikingly, we observed that only crRNAs directed against the plus-genomic RNA demonstrated antiviral activity in the replicon assay, in contrast to those that bind the minus-genomic RNA, the replication intermediate. These results point to a major difference in the vulnerability and biology of the +RNA versus −RNA strands of the SARS-CoV-2 genome and provide important insights for the design of RNA-targeting antivirals.